Can the tricyanomethanide anion improve CO2 absorption by acetate-based ionic liquids?. Issue 19 (4th May 2017) - Lepre, L. F.; Szala-Bilnik, J.; Pison, L.; Traïkia, M.; Pádua, A. A. H.; Ando, R. A.; Costa Gomes, M. F.
Abstract : The chemical reaction of carbon dioxide with 1-alkyl-3-methylimidazolium acetate ionic liquids is not affected by presence of the C(CN)3 − anion, which leads to a faster gas absorption and a higher solubility. Abstract : Carbon dioxide absorption by mixtures of two ionic liquids with a common cation—1-butyl-3-methylimidazolium acetate, [C4 C1 Im][OAc], and 1-butyl-3-methylimidazolium tricyanomethanide, [C4 C1 Im][C(CN)3 ]—was determined experimentally at pressures below atmospheric pressure as a function of temperature between 303 K and 343 K, and at 303 K as a function of pressure up to 10 bar. It is observed that the absorption of carbon dioxide decreases with increasing tricyanomethanide anion concentration and with increasing temperature, showing a maximum of 0.4 mole fraction of carbon dioxide in pure [C4 C1 Im][OAc] at 303 K. At this temperature, the CO2 absorption in the mixtures [C4 C1 Im][OAc](1− x ) [C(CN)3 ] x is approximately the mole-fraction average of that in the pure ionic liquids. By applying an appropriate thermodynamic treatment, after identification of the species in solution, it was possible to calculate both the equilibrium constant, K eq, and Henry's law constant, K H, in the different mixtures studied thus obtaining an insight into the relative contribution of chemical and physical absorption of the gas. It is shown that chemical sorption proceeds through a 1 : 2 stoichiometry between CO2 and acetate-based ionic liquid. The presence of the C(CN)3 − anion does not significantly affect the chemical reaction of the gas with the solvent ( K eq = 75 ± 2 at 303 K) but leads to lower Henry's law constants (from K H = 77.8 ± 0.6 bar to K H = 49.5 ± 0.5 bar at 303 K), thus pointing towards larger physical absorption of the gas. The tricyanomethanide anion considerably improves the mass transfer by increasing the fluidity of the absorbent as proven by the larger diffusivities of all the ions when the concentration of the C(CN)3 − anion increases in the mixtures.